2020
DOI: 10.1371/journal.pone.0241515
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide DNA methylation analysis of breast cancer MCF-7 / Taxol cells with MeDIP-Seq

Abstract: Breast cancer (BC) is the most frequently diagnosed tumor in women worldwide. Although the combination of surgery and Taxol chemotherapy can achieve a certain therapeutic effect, patients often develop drug-resistance, resulting in a poor prognosis. Therefore, it is significative to seek the molecular mechanism of chemotherapy resistance. Recent studies have found that abnormal epigenetic regulation in breast cells changes the expression of key genes, which can lead to the occurrence, development, and maintena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…In addition, this study assessed the correlation between GSDME and p-GP using the UALCAN dataset. Correlation analysis showed that tissues with higher GSDME expression had lower p-GP protein (Fig 2C) (R = −0.34, P <0.01), which was consistent with the results of previous research [31].…”
Section: Plos Onesupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, this study assessed the correlation between GSDME and p-GP using the UALCAN dataset. Correlation analysis showed that tissues with higher GSDME expression had lower p-GP protein (Fig 2C) (R = −0.34, P <0.01), which was consistent with the results of previous research [31].…”
Section: Plos Onesupporting
confidence: 91%
“…We used a low concentration gradient induction method to establish the Taxol-resistant MCF-7 /Taxol cells [31]. MCF-7 cells during logarithmic growth were seeded in a 25cm 2 six-well culture plates and cultured for 12h.…”
Section: Construction Of Taxol-resistant Cell Lines For Breast Cancermentioning
confidence: 99%
“…This phenomenon, by changing the expression of tumor suppressor or oncogenic genes and their promoters and/or enhancers, is involved in cancer initiation, progression, and even chemoresistance. In experimental models of breast cancer, exposure of MCF-7 cells to paclitaxel in a low-concentration gradient induction method (aimed at promoting chemoresistance) showed an overall increase in DNA methylation pattern ( Shi et al, 2020 ). To overcome this chemoresistance, the co-exposure of breast cancer cell lines to taxanes and phenethyl isothiocyanate (an epigenetic agent) was able to restore chemosensitivity ( Liu et al, 2013 ).…”
Section: Medical Properties Of Taxanesmentioning
confidence: 99%
“…MeDIP, coupled with massively parallel NGS, is a cost-effective method even suitable for minute clinical samples and has been demonstrated as an effective technique for methylation investigation [ 16 , 17 ]. Many cancer studies employed this technique to identify DMGs (Differentially Methylated Genes), such as breast cancer [ 18 ], ovarian cancer [ 19 ], pancreatic cancer [ 20 ], and others. In this study, we have analyzed the methylation profile of ovarian cancer samples using methylated DNA immunoprecipitation combined with high-throughput sequencing (MeDIP-seq) by Illumina NextSeq 500 platform, which employs an anti-cytosine antibody resulting in the enrichment of methylated DNA.…”
Section: Introductionmentioning
confidence: 99%